Potassium Isotope Evidence for Origin of Archean TTG Rocks From Seawater‐Hydrothermally Altered Oceanic Crust - D.‐Y. Xiong; X.‐L. Wang; W. Li; Y.‐F. Zheng; C. R. Anhaeusser; A. Hofmann; D. Wang; J.‐Y. Li (Geochemistry, Geophysics, Geosystems)
Abstract Tonalite‐trondhjemite‐granodiorite (TTG) rocks constitute a crucial part of the Archean continental crust, yet their origins remain contentious. It is critical to decipher their source nature and hydration mechanism. This paper presents a study of whole‐rock K stable isotopes in well‐preserved ca. 3.51–3.42 Ga TTG rocks and associated mafic rocks from the Barberton granitoid‐greenstone terrane (BGGT) in the Kaapvaal Craton, South Africa. The results show for the first time a substantial δ41K variation from −0.69 ± 0.07‰ to −0.32 ± 0.05‰ (2SD) for the Paleoarchean mafic rocks, exceeding the present mantle δ41K range from −0.6 to −0.3‰. This variation can be well explained by the seawater‐hydrothermal alteration at different temperatures. Similarly, the Paleoarchean TTGs exhibit a wide δ41K range from −0.55 ± 0.04‰ to 0.07 ± 0.08‰ (2SD). In combination with available zircon δ18O values of 5.07–6.02‰, it is evident that Archean TTGs would be derived from partial melting of the seawater‐hydrothermally altered oceanic crust (AOC). The distinct K‐O isotope signatures demonstrate that the hydration of Archean mafic crust is caused by the hydrothermal alteration at mid‐ocean ridges during seafloor spreading. The variable K‐O isotope compositions in the Archean TTGs signify a series of processes that are dominated by the seawater‐hydrothermally altered AOC in a Wilson cycle from divergence through convergence to rifting of Archean oceanic plates. This offers a viable mechanism for TTG petrogenesis and the growth of continental crust in the Archean.